EP1004 Prognostic impact of BRCA2 mRNA expression in ovarian cancer: validation using the TCGA cohort. (1st November 2019) - Tsibulak, I; Hackl, H; Wieser, V; Welponer, H; Degasper, C; Leitner, K; Knoll, K; Fiegl, H; Zeimet, AG; Marth, C
Abstract : Introduction/Background: Mutations in cancer susceptibility genes BRCA1/2 are considered to be associated with better survival in ovarian cancer (OC) patients possibly due to a better response to platinum based chemotherapy and PARP inhibitors. However, the impact of the BRCA1/2 mRNA-expression is not well characterized in OC, but could also influence the platinum response and thus predict the clinical outcome in OC patients. Our previous studies have shown that low BRCA1-expression was associated with favorable overall survival (OS) and low BRCA2-expression with better progression-free survival (PFS) and OS in 201 OC patients. The aim of the present study was to validate the prognostic impact of BRCA expression in OC using the TCGA (The Cancer Genome Atlas) cohort. Methodology: Clinical and genomic data were obtained from the OC Dataset of The Cancer Genome Atlas (n=581). Overall and progression free survival was estimated using Kaplan-Meier plots and Cox-Regression. Optimal cut off points were defined using Youden index. Results: Univariate survival analysis showed that low BRCA2 expression was associated with favorable PFS (p=0.029) and OS (p=0.011). Multivariable survival analysis confirmed the prognostic value of BRCA2 expression both for PFS and OS. Conclusion: Low expression of BRCA2 predicts better survival in patients with OC. Our findings may reflect higher platinum-sensitivity due to reduced capacity of DNA damage repair in tissues with low BRCA2 expression. In this context, especially in BRCA-wildtype cancers BRCA2 expression could also be potential predictor for PARP sensitivity. Disclosure: Nothing to disclose.